Rural Library Staffs' Competencies in the Information Society - Shaifuddin, Norshila; Noordin, Siti Arpah; Sani, Mad Khir Johari Abdullah; Mokhtar, Wan Nor Haliza Wan (Journal of Informatics and Mathematical Sciences, 2017)
The role of a rural library in developing an information society has long been realized by the government. The literature review indicates that the growth of the information society has forced the work environment and of librarians, especially in delivering services to the communities. Therefore, the rural libraries are being subjected to respond to the new changes. To ensure them to participate in the information society, there have to be appropriately trained workers in place; the rural librarian is required to put the element that promotes the use of information and rural library resources effectively. They should strengthen the function of a rural library staff as information intermediaries and increased their competencies to enable them to teachlibrary users to use the information they need for. The required competencies will be discussed in this paper.